Slope Stability of Darbendikhan Dam Site and Near Surroundings. A Reconnaissance Study, Kurdistan Region, NE Iraq - Sissakian, Varoujan K.; Sdiq, Sakar A.; Haris, Govar K. (Sulaimani Journal for Pure and Applied Sciences, 2018)
Darbendikhan Dam is constructed on the Sirwan (Diyala) River during 1955- 1961. The dam is of earth fill type with concrete spill ways and gates for electric power generation. The dam axis is almost E – W with both left and right abutments being constructed within the Gercus Formation, which consists of red clastics with more claystones. The Gercus Formation is overlain by the Pila Spi Formation that consists of hard to very hard, well bedded carbonates. The Pila Spi Formation is overlain by the Fatha Formation that consists of thick reddish brown claystones alternated with thin gypsum and limestone beds. Both Gercus and Fatha formations form steep to very steep slopes on upstream and downstream, respectively. All the slopes on the dam site and near surroundings suffer from different types of mass movements with different sizes. Some of them are old and dormant; others are recent and active exhibiting geological hazards, which may cause large loss of human life and the existing properties and infrastructure. We studied the slopes using different types of satellite images with different resolutions and conducted field trips to the dam site to collect data. We recommended some precautions to make the slopes more stable.
Keywords: Slope stability; Darbendikhan Dam; Mass movements; Geological Hazards